The pathogenesis of idiopathic normal pressure hydrocephalus based on the understanding of AQP1 and AQP4 - Zhao, Zitong; He, Jian; Chen, Yibing; Wang, Yuchang; Wang, Chuansen; Tan, Changwu; Liao, Junbo; Xiao, Gelei (Frontiers in Molecular Neuroscience, 2022)
Idiopathic normal pressure hydrocephalus (iNPH) is a frequent neurological disorder without a recognized cause. Aquaporins (AQPs) are transmembrane channels that carry water through cell membranes and are critical for cerebrospinal fluid circulation and cerebral water balance. The function of aquaporins in developing and maintaining hydrocephalus should be studied in greater detail as a possible diagnostic and therapeutic tool. Recent research indicates that patients at iNPH consume more Aquaporin 4 (AQP4) and Aquaporin 1 (AQP1), suggesting that these AQPs are essential in creating iNPH. The expression, function, and regulation of AQPs in iNPH are being examined to identify new research issues and objectives.